Application of the rules on psychological harassment by the European Union institutions, bodies, offices and agencies covered by Regulation No 31 (EEC), 11 (EAEC) and their interpretation by the EU courts - Morica, Dina (Riga Graduate School of Law, 2023)
The purpose of this Master Thesis is to assess whether, under the existing rules, the European Union (hereinafter – “the EU”) institutions, bodies, offices and agencies (hereinafter – “the institutions”) covered by Regulation No 31 (EEC), 11 (EAEC) afford their staff members effective protection against psychological harassment. Accordingly, the research question of the Master Thesis is: How the rules on psychological harassment are applied by the institutions and interpreted by the EU Courts? The Master Thesis finds that the burden of proof is particularly high for an alleged victim as they must prove what they allege while an alleged harasser benefits from the presumption of innocence. The Master Thesis identifies such duties of the institutions as the duty to provide assistance, the duty to open and conduct an administrative inquiry, the duty to separate an (alleged) harasser from an (alleged) victim of psychological harassment, the duty to protect privacy of the involved persons, etc. The author suggests, inter alia, to enhance regulatory acts adopted by each institution to prevent psychological harassment and conduct administrative inquiries and disciplinary procedures, as well as advocates placing the responsibility for preventing psychological harassment in a legislative act, i.e. Regulation No 31 (EEC), 11 (EAEC) rather than a regulatory act, thus giving greater importance to this issue.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Labour law; Psychological harassment; Regulation No 31 (EEC), 11 (EAEC)